ISOLATED SEAFLOOR POCKMARKS LINKED TO BSRS, FLUID CHIMNEYS, POLYGONAL FAULTS AND STACKED OLIGOCENE-MIOCENE TURBIDITIC PALAEOCHANNELS IN THE LOWER CONGO BASIN - Gay A.; Lopez M.; Séranne M.; Cochonat P.; Levaché D.; Sermondadaz G. (My University, 2006)
Based on high-resolution 3D seismic data sets, we document the subsurface reservoir architecture and organization of a portion of the Oligocene-Miocene stratigraphy within the Congo Basin, offshore southwestern Africa. Within the 3D seismic volume, we have identified four levels of turbiditic palaeochannels, which are separated by low-amplitude continuous reflectors interpreted as hemipelagic sediments. Geochemical analyses on sediment samples taken within overlying seafloor pockmarks reveal the presence of thermogenic gases and oils, suggesting that deep-seated fluids have migrated through both the channel deposits and the impermeable layers between them, forming a conduit to the surface. Deep thermogenic fluids produced within Cretaceous source rocks are preferentially entrapped within coarse-grained turbiditic Oligocene-Miocene palaeochannels. We show in this study that the vertical stacking pattern of turbiditic palaeochannels allows the best pathway for fluids migration. Once the fluids migrate to the upper layer (i.e., Upper Miocene) of palaeochannels, they can reach the seafloor via migration along a highly faulted interval composed of polygonal faults. They are temporarily inhibited below an interpreted 300-m-thick gas hydrate layer marked by a strong BSR on seismic profiles. Fluids accumulate under the hydrate stability zone to form a thick layer of free gas. The generation of excess pore fluid pressure in the free gas accumulation leads to the release of fluids along faults of the highly faulted interval forming pockmarks on the seafloor. Ultimately, we show in this study that fluids are progressively concentrated in the sedimentary column and aligned pockmarks on the seafloor may represent a focused fluid flow from stacked turbiditic palaeochannels. © 2005 Elsevier B.V. All rights reserved.
Keywords: BSR; FLUID CHIMNEYS; FLUID MIGRATION; HYDRATES; PIPES; POCKMARKS; POLYGONAL FAULTS; TURBIDITIC PALAEOCHANNELS; Cretaceous; Miocene; Oligocene; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен